A Case of Ameloblastic Fibrodentinoma in the Posterior Maxilla - Mochizuki, Akane; Fukui, Rei; Amemiya, Toshihiko; Arai, Yoshinori; Asano, Masatake (UI Scholars Hub, 2021)
Ameloblastic fibrodentinoma (AFD) is a rare tumor with an incidence rate of less than 1%. When lesion with the histomorphology of ameloblastic fibroma(AF), which is true neoplasms, form dysplastic dentin, and had been referred to as AFD. It histologically consists of odontogenic ectomesenchyme resembling the dental papilla, epithelial strands, and nests resembling dental lamina and enamel organ with dentin formation. Although newly categorized as an odontoma by the WHO in 2017, this lesion was previously referred to as a rare odontogenic tumor by the WHO in 2005. Objective: We aim to summarize our case with other previous case reports considered to be equivalent to the conventional WHO classification of AFD. Case Report: An 8-year-old girl presented to our hospital complaining of delayed eruption of a tooth. Computed tomography showed an odontoma-like radiopacity in a unilocular radiolucent lesion sized approximately 20 mm. The lesion was extracted under general anesthesia and histopathologically exhibited AFD. Herein, we report a rare case of AFD in the maxilla. Conclusion: Although this lesion deviates from the concept of disease as an odontogenic tumor, it is hoped that clinically sufficient follow-up is required and more similar cases will accumulate as independent tumors, rather than simply being recognized as developmental odontomas.